Peri-Implant Soft Tissue Management through Use of Cultured Gingival Graft: A Case Report - Mohammad Mohammadi; Rasool Mofid; Mohammad Ali Shokrgozar (Acta Medica Iranica, 2011)
Tissue-engineered gingival graft was used for regenerating facial gingiva around an implant at lower left first premolar area with insufficient attached gingiva. Engineered gingival graft was produced by mixing 250 ml bovine skin collagen with 250 ml nutritional medium containing human gingival fibroblasts (2×105). 3 months post-surgery, there were gains in the attached gingiva compared to pre-surgery. The histological examination revealed a keratinized tissue on the treated site. Based on the result of this investigation, this graft was safe and capable of generating keratinized gingiva.